Adolescent brain cognitive development (ABCD) study: Overview of substance use assessment methods. (August 2018) - Lisdahl, Krista M.; Sher, Kenneth J.; Conway, Kevin P.; Gonzalez, Raul; Feldstein Ewing, Sarah W.; Nixon, Sara Jo; Tapert, Susan; Bartsch, Hauke; Goldstein, Rita Z.; Heitzeg, Mary
Abstract: One of the objectives of the Adolescent Brain Cognitive Development (ABCD) Study (https://abcdstudy.org/ ) is to establish a national longitudinal cohort of 9 and 10 year olds that will be followed for 10 years in order to prospectively study the risk and protective factors influencing substance use and its consequences, examine the impact of substance use on neurocognitive, health and psychosocial outcomes, and to understand the relationship between substance use and psychopathology. This article provides an overview of the ABCD Study Substance Use Workgroup, provides the goals for the workgroup, rationale for the substance use battery, and includes details on the substance use module methods and measurement tools used during baseline, 6-month and 1-year follow-up assessment time-points. Prospective, longitudinal assessment of these substance use domains over a period of ten years in a nationwide sample of youth presents an unprecedented opportunity to further understand the timing and interactive relationships between substance use and neurocognitive, health, and psychopathology outcomes in youth living in the United States.